Technical Report. Rapid market assessment: viable sweetpotato technologies in Africa-Tanzania - Mayanja, S.; Grant, F.; Kakuhenzire, R.; Okuku, H.S. (International Potato Center, 2017)
This report is based on a rapid assessment study conducted in 14 markets in the intervention areas of the Viable Sweetpotato Technologies in Africa (VISTA) Tanzania project. We would like to thank the male and female traders, consumers and local government partners in Tanzania who participated in the study. We believe that this report captures their voices, interests and hopes and we hope that the findings will be a significant contribution in improving sweetpotato interventions in not only Tanzania but also other parts of Africa where the VISTA project is being implemented.